Museum Docents’ Understanding of Interpretation - Amanda C. Neill (Adult Education Research Conference, 2010)
This basic interpretive qualitative study explored docents’ perceptions of their interpretive role and sought to determine how those perceptions shape docents’ practice. The conceptual frameworks of hermeneutics and symbolic interactionism inform the study. The study offers a view into the world of volunteer adult educators in non-formal education settings.